Faktor Pendorong Wisatawan Malaysia Berkunjung ke Sumatera Barat - Nelvi Susgenti (Journal of Economics and Management Scienties, 2022)
The background of this research is to identify the motivations factors which become the background the visiting of malaysian to West Sumatera and to identify group / segmentation of tourist based on motivation in journey to West Sumatera. The research population is the tourist from malaysia that visit west sumatera . the sample in this research is international tourist, not the visitor working intention or diplomatic guest. From the result of the research it is found that the factors which stimulate the tourist motivation from malaysia who visit West Sumatera are presitige, culture, medical treatmentl, natural view, leasure and fresh air. In fact , the dominan motivation in visiting West Sumatera are prestige and pride factor. Meanwhile market segmentation based on tourist motivation that visit West Sumatera , which are : fresh air, the natural beauty and culture.